(3GdGcJaGA ef JGQjN GdNdaGA Ch HJGQjN GdNdaGAs - (3eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, GHf fHGJg , LeGd GdOjf CHh HcQ,J (B768 (3g` s
(3ChdgG (B:s
(3Qhi GHh GSYO GdSGYOi Gf GdfHi Udi Gddg Ydjg hSde bGd ddYHGS jG CHj GdaVd dCHQe efRdc ZOkG CfJ hHfhc s
(3BNQgG (B:s
(3ef GdYLH Gfg hdi GdhRGQI dKdGK NdaGA GdebJOQ hGdbGgQ hGdQGVi hSGaQ KdGK SaQGJ GKfjf eJNajG Edi TjQGR hhGMOI ai hRGQJg Edi GdehUd hfbd HYO ehJg KdGK eQGJ s
(3Vef eLehY , JQJjHgG (B: (3GdKGfjs
(3jHJOF HCNHGQ GdNdaGA ef Hfi GdYHGS Edi NdGaI GdQVi HGddgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B47 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B28 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs